Awareness of age-related change is associated with attitudes toward technology and technology skills among older adults - Schlomann, Anna; Memmer, Nicole; Wahl, Hans-Werner (Frontiers in psychology, 2022)
Despite much research in the context of aging and technology, the role of Views on aging (VoA) for differences in technology use and attitudes among older adults has rarely been studied so far. This study focuses on the associations between a multidimensional measure of VoA and technology use, technology skills, and attitudes toward technology in a sample of older adults (n = 369, age range: 65–93 years, 48.2% male).